Pertukaran Data Antar Database Dengan Menggunakan Teknologi API - Hanafi, Ahmad; Sukarsa, I Made; Agung Cahyawan Wiranatha, A.A. Ketut (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2017)
Electronically data interchange between institutions or companies must be supported with appropriate data storage media capacity. MySQL is a database engine that is used to perform data storage in the form of information, where the data can be utilized as needed. MYSQL has the advantage of which is to provide convenience in terms of usage, and able to work on different platforms. System requirements that must be reliable and multitasking capable of making the database not only as a data storage medium, but can also be utilized as a means of data exchange. Dropbox API is the best solution that can be utilized as a technology that supports the database to be able to Exchange data. The combination of the Dropbox API and database can be used as a very cheap solution for small companies to implement data exchange, because it only requires a relatively small Internet connection.
Keywords: Pertukaran Data Elektronik; Database; MySQL; Dropbox API; Internet.